2020
DOI: 10.1007/978-3-030-33208-2_4
|View full text |Cite
|
Sign up to set email alerts
|

Marine Micro- and Macroalgae in the Polar Night

Abstract: The chapter illucidates aspects of the ecology of micro-and macroalgae with a focus on the dark sesason. It comprises of six parts and starts with an introduction (4.1) about Arctic marine micro-and macroalgae. Section 4.2 reviews the key abiotic environmental variables related to micro-and macroalgae growth and survival. The description of the different groups of microalgae are shown in section 4.3, comprising phytoplankton, microphytobenthos and seaice algae. Section 4.4 describes the three classes of macroa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 106 publications
(154 reference statements)
3
28
0
Order By: Relevance
“…The initiation of an UIB requires a viable seed population of algal cells present in the euphotic zone of the water column under the ice. There are three potential seeding sources for UIBs: (a) algal cells in the water column, (b) vegetative cells or resting stages at the sediment surface, and (c) algal cells or resting stages entrapped in sea ice that are released during melt onset at the underside of the ice (Johnsen et al, 2020). Very little is known about the relative importance of these three different seeding strategies, but it likely varies strongly depending on mixing depth, bottom topography, and sea-ice conditions.…”
Section: Diversity Of Under-ice Blooms: Phenology Strategy Assemblamentioning
confidence: 99%
See 1 more Smart Citation
“…The initiation of an UIB requires a viable seed population of algal cells present in the euphotic zone of the water column under the ice. There are three potential seeding sources for UIBs: (a) algal cells in the water column, (b) vegetative cells or resting stages at the sediment surface, and (c) algal cells or resting stages entrapped in sea ice that are released during melt onset at the underside of the ice (Johnsen et al, 2020). Very little is known about the relative importance of these three different seeding strategies, but it likely varies strongly depending on mixing depth, bottom topography, and sea-ice conditions.…”
Section: Diversity Of Under-ice Blooms: Phenology Strategy Assemblamentioning
confidence: 99%
“…This leads to extended periods where ambient irradiances are not sufficient for in situ primary production in ice-free surface waters (Kvernvik et al, 2018), and even less so underneath sea-ice cover (see also the previous section "Physiological Phytoplankton Assemblage Responses to Varying Light Regimes"). Phytoplankton have adapted through various strategies to cope with these conditions, ranging from mixotrophy/heterotrophy, resting stage formation, and utilization of internal lipid stores to survival of vegetative cells with lowered metabolic activity (Johnsen et al, 2020). Phytoplankton communities during wintertime are characterized by very low cell concentrations and a predominance of small, flagellated cells, as well as heterotrophic dinoflagellates (Lovejoy et al, 2007;Błachowiak-Samołyk et al, 2015;Brown et al, 2015;Vader et al, 2015).…”
Section: Diversity Of Under-ice Blooms: Phenology Strategy Assemblamentioning
confidence: 99%
“…This synchronization allows the acquisition and accumulation of energy and an efficient energy transfer to higher trophic levels. The dark winter season is particularly poorly studied for activity of phyto-and zooplankton, although recent research demonstrated that this season is by no means a period of inactivity, and several trophic levels remain active and complete important parts of the life cycles in the dark season (Berge et al, 2020;Johnsen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the polar night is of key interest, when physical mixing [24][25][26] and microbial recycling of detrital and inorganic matter 27,28 replenishes nutrients to fuel the subsequent phytoplankton bloom. Arctic phototrophic taxa are thought to persist in dormancy 29 , responding rapidly when light and stratification return 30 .…”
Section: Introductionmentioning
confidence: 99%